PERSEPSI MASYARAKAT TENTANG OBJEK WISATA KEBUN TEH PERSEROAN TERBATAS PERKEBUNAN NUSANTARA (PTPN) VI DANAU KEMBAR KABUPATEN SOLOK - BR.Damanik, Juwita Melati Sari; Ahmad, Ridwan; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
Tourism developmen would be supported by all levels, be it the government, private sector and comunities. The results of field observation by the author, yet all walks of life to support the implementation of tourism activities in solok regency, pablic perception of tea gardens attraction Twins Lake in Solok regency This study aimed to obtain information, analyze: public perceptions of the Tea Garden Perkebunan Nusantara VI (PTPN VI) Danau Kembar Solok regency views of : 1) the perception of security, 2) perception of order, 3) perception of cleanliness, 4) perception of coolness, 5) perception of beauty, 6) perception of hospitality and 7) perception of memories.Â This research is a descriptive qualitative study, carried out at Tea Gardens attraction in Perkebunan Nusantara VI (PTPN VI) Danau Kembar of Gunung Talang Solok regency. Research informants taken snowball sampling, such as the people who were around attractions, including the Department of Tourism Solok district, villages guardian, trustee ellipse, visitors and people who live around objects Tea Garden Perkebunan Nusantara VI (PTPN VI) Danau Kembar Solok regency.Â Research results showed both the public perception of the safety of the object Tourism Garden Tea Perkebunan Nusantara VI (PTPN VI) Danau Kembar Solok regency, further public has a poor perception of the order, the public has a good perception of the cleanliness. Sapta charm furthermore, people have a very good perception about the security. Furthermore people have a very good, society has a pretty good perception of the object Tourism hospitality at and community have a very good perception of object memories in Tea Garden Perkebunan Nusantara VI (PTPN VI) Danau Kembar Solok regency.